Volatile Constituents of the Aerial Parts of Ferulago subvelutina Rech. f., Ferulago stellata Boiss., Leaves and Flowers of Prangos ferulacea (L.) Lindle. and Leaves of Ferula ovina (Boiss.) Boiss.: Four Umbelliferae Herbs from Iran - Taherkhani, Mahboubeh; Rustaiyan, Abdolhossein; Masoudi, Shiva (Asian Journal of Chemistry, 2011)
The composition of the essential oils from four umbelliferae species of Iran i.e., Ferulago subvelutina Rech. f. (syn. Ferulago turcomanica Schischk.), Ferulago stellata Boiss. (syn. Ferulago koeiziana Rech. f.), Prangos ferulacea (L.) Lindle. (syn. Prangos macrocarpa Boiss., Cachrys goniocarpa Boiss., Cachrys prangoides Boiss.) and Ferula ovina (Boiss.) Boiss. obtained by hydrodistillation were analyzed by GC and GC/MS. The major constituents of the oil of F. subvelutina appeared to be limonene (27.0 %), a-phellandrene (23.1 %) and a-pinene (13.3 %) and the main composition of F. stellata was 2,4,5-trimethyl benzaldehyde (61.1%). b-Pinene (29.6 % and 20.6 %), a-pinene (19.8 % and 8.8 %), d-3-carene (11.4 % and 10.4 %) and b-phellandrene (11.1 % and 8.1 %) were the main constituents in the leaf and flower oils of P. ferulacea, respectively. The leaf oil of F. ovina was characterized by higher amount of a-pinene (22.5 %), bornyl acetate (14.1 %) and camphene (11.0 %).